Endoplasmic Reticulum Stress and Unfolded Protein Response in Vernal Keratoconjunctivitis - Leonardi, Andrea; Donato, Alice; Rosani, Umberto; Di Stefano, Antonino; Cavarzeran, Fabiano; Brun, Paola (Investigative ophthalmology & visual science, 2024)
Vernal keratoconjunctivitis (VKC) is an ocular allergic disease characterized by a type 2 inflammation, tissue remodeling, and low quality of life for the affected patients. We investigated the involvement of endoplasmic reticulum (ER) stress and unfolded protein response in VKC. Conjunctival imprints from VKC patients and normal subjects (CTs) were collected, and RNA was isolated, reverse transcribed, and analyzed with the Affymetrix microarray. Differentially expressed genes between VKC patients and CTs were evaluated. Genes related to ER stress, apoptosis, and autophagy were further considered. VKC and CT conjunctival biopsies were analyzed by immunohistochemistry (IHC) with specific antibodies against unfolded protein response (UPR), apoptosis, and inflammation. Conjunctival fibroblast and epithelial cell cultures were exposed to the conditioned medium of activated U937 monocytes and analyzed by quantitative PCR for the expression of UPR, apoptosis, autophagy, and inflammatory markers. ER chaperones HSPA5 (GRP78/BiP) and HYOU1 (GRP170) were upregulated in VKC patients compared to CTs. Genes encoding for ER transmembrane proteins, PKR-like ER kinase (PERK), activating transcription factor 6 (ATF6), ER-associated degradation (ERAD), and autophagy were upregulated, but not those related to apoptosis. Increased positive reactivity of BiP and ATF6 and unchanged expression of apoptosis markers were confirmed by IHC. Cell cultures in stress conditions showed an overexpression of UPR, proinflammatory, apoptosis, and autophagy markers. A significant overexpression of genes encoding for ER stress, UPR, and pro-inflammatory pathway components was reported for VKC. Even though these pathways may lead to ER homeostasis, apoptosis, or inflammation, ER stress in VKC may predominantly contribute to promote inflammation.